The Influence of Family Environment on Learning Atten-tion and Learning Facilities at SD Negeri 1 Centre Pattal-lassang - Nuraliah Nuraliah; Elpisah Elpisah; Saripuddin Saripuddin; Erni Rismawati; Suarlin Suarlin (International Journal of Humanities and Social Sciences Reviews, 2025)
Family environments play a crucial role in shaping students’ learning processes, particularly at the primary education level. This study aims to examine the effect of the family environment on learning attention and the fulfillment of learning facilities and infrastructure among Grade VI students at UPT SD Negeri 1 Centre Pattallassang. Using a quantitative associative approach with an ex post facto design, data were collected from 85 students through a structured questionnaire and analyzed using descriptive statistics, simple linear regression, and canonical correlation analysis. The results indicate that the family environment has a positive and significant effect on learning attention (B = 0.631, p < 0.001) and on the fulfillment of learning facilities and infrastructure (B = 0.723, p < 0.001). The family environment explains 42.1% of the variance in learning attention and 48.6% of the variance in the fulfillment of learning facilities. Canonical correlation analysis further reveals a strong simultaneous relationship between the family environment and the combined outcomes of learning attention and learning facilities. These findings highlight the central role of the family as a key educational microsystem that supports both cognitive–affective engagement and material learning conditions. The study underscores the importance of strengthening school–family collaboration and family-based support strategies to enhance learning quality in primary education.